Optimizing Social Media Marketing to Preserve Lombok's Traditions and Culture - Iswanto, Dedy; Irsyad, Ziqrurrahman; Istiqlal; Sangadji, Suwandi S. (Apollo: Journal of Tourism and Business, 2024)
This research examines the impact of Social Media Marketing on preserving local wisdom on Lombok Island. By employing quantitative methods and multiple linear regression, the study evaluated five independent variables: social media marketing content (X1), user interaction on social media (X2), paid advertising on social media (X3), entertainment and trends on social media (X4), and Electronic Word-of-Mouth (e-WOM) (X5), on the preservation of local traditions and culture (Y). Data from 108 randomly selected participants revealed that user interaction on social media (X2) exerted the most significant influence on the preservation of local traditions and culture, with a coefficient of 0.532 and a t-value of 5.108, significant at p < 0.001. The other variables—content marketing, paid advertising, entertainment, and e-WOM—did not exhibit significant effects. These results indicate that marketing strategies emphasizing active user engagement on social media are more effective in promoting the preservation of local wisdom. Consequently, it is advised that programs aimed at preserving local traditions and culture should prioritize enhancing user interaction on social media, complemented by a holistic approach integrating diverse marketing and community engagement techniques.